The Governing-Evaluation-Knowledge Nexus Swedish Higher Education as a Case - Segerholm, Christina; Hult, Agneta; Lindgren, Joakim; Rönnberg, Linda (Evaluating Education: Normative Systems and Institutional Practices, 2019)
XVII, 208 p. 4 illus.